The deadline clock eaudiobook - Deaver, Jeffery (Colter Shaw, 2022)
Reward seeker Colter Shaw faces a ticking clock with murderous consequences in this riveting short story. A serial kidnapper is on the loose in a small town in Maine, targeting wealthy women and demanding a huge ransom in bitcoin for their safe return. When his latest victim’s husband claims that he can’t come up with the money, the word “deadline” takes on a disturbingly literal meaning. The local police are out of their depth, but Colter Shaw takes the lead in the investigation. Soon, he’s using his survivalist instincts to uncover clues and pursue suspects, putting his own life on the line to catch the would-be killer before the countdown hits zero.